The role of helophyte species on nitrogen and phosphorus retention from wastewater treatment plant effluents. (15th December 2019) - Gacia, Esperança; Bernal, Susana; Nikolakopoulou, Myrto; Carreras, Ester; Morgado, Laura; Ribot, Miquel; Isnard, Manel; Sorolla, Albert; Sabater, Francesc; Martí, Eugènia
Abstract: In the Mediterranean region, water scarcity compromises stream water quality particularly downstream of wastewater treatment plants (WWTP). We tested the potential of four helophyte species to reduce dissolved inorganic nitrogen (N) and phosphorus (P) from WWTP effluents. We conducted an 11-month mesocosm experiment to assess differences in N and P content among plant compartments and among species. Moreover, we quantified the relative contribution of above and belowground parts of the plants to N and P retention. The experiment was conducted at the Urban River Laboratory (www.urbanriverlab.com ) in artificial channels (12 m long x 0.6 m wide x 0.4 m deep) planted with monospecific stands of Iris pseudoacorus, Typha angustifolia, Phragmites australis and Scirpus lacustris . Channels (three replicates per species) received water from the WWTP effluent, which flowed at a constant rate of 5 L min −1 through the sub-surface. The helophytes were planted in November 2014 and biomass standing stocks of carbon (C), N and P were measured in October 2015 at the time of maximum plant biomass. Differences in the concentration of N and P were larger among plant compartments than among species. The highest N concentration was measured in leaves while rhizomes showed the highest P concentration. The total plant biomass varied greatly among species from 11.4 to 4.6 Kg DW m −2 for Iris and Scirpus, respectively. Iris accumulated the highest amount of N (256 g N m −2 ) and P (27 g P m −2 ) in biomass. Plants retained from 8% ( Scirpus ) to 19% ( Iris ) of total dissolved inorganic N inputs to the channels (10.4 kg N) during the experiment, and from 6% ( Phragmites ) to 14% ( Iris ) of total dissolved inorganic P inputs (1.3 kg P). This study provides quantitative evidence to water managers of the potential role of helophytes to improve water quality in freshwater ecosystems receiving water from WWTP effluents. Graphical abstract: Image 1 Highlights: Helophytes can retain substantial amounts of N and P from WWTP effluents. Nutrient concentration varied largely among plant compartments than among species. Iris has high capacity to retain N and P, followed by Typha. Scirpus and Phragmites have low capacity to retain N and P, respectively. Helophytes retention represented 8–19% of N and 8–14% of P from WWTP effluent.